2021
DOI: 10.7759/cureus.18263
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of Doctors and Patients in Starting Insulin for Type 2 Diabetes Mellitus

Abstract: BackgroundManagement of patients with type 2 diabetes mellitus (T2DM) may involve insulin therapy. However, this treatment may be avoided or delayed by physicians or patients due to the presence of certain barriers. This study aimed to evaluate the barriers to initiating insulin therapy for both physicians and patients with T2DM. MethodThis was a cross-sectional, questionnaire-based study. Data related to the physicians' personal and professional experience were collected, and 15 barriers to initiating insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…8,9 However, because of the barriers associated with using insulin, patients and prescribers may prefer to use combination oral drugs over insulin. 23,24 Consistent with this study finding, Wang et al 25 reported that 92% of participants in their study were started on single ADDs. The result was also in keeping with the studies by Lee et al 26 (2021) and Chu et al, 17 who showed a significant increase in combinationtherapy prescribing for T2DM management in Korea (between 2000 and 2019) and Taiwan (between 2005 and 2012), respectively; however, it was not stated in these studies at which treatment stage the prescribing pattern was observed.…”
Section: Discussionsupporting
confidence: 76%
“…8,9 However, because of the barriers associated with using insulin, patients and prescribers may prefer to use combination oral drugs over insulin. 23,24 Consistent with this study finding, Wang et al 25 reported that 92% of participants in their study were started on single ADDs. The result was also in keeping with the studies by Lee et al 26 (2021) and Chu et al, 17 who showed a significant increase in combinationtherapy prescribing for T2DM management in Korea (between 2000 and 2019) and Taiwan (between 2005 and 2012), respectively; however, it was not stated in these studies at which treatment stage the prescribing pattern was observed.…”
Section: Discussionsupporting
confidence: 76%
“…This is caused by several factors, including loss to follow-up, insufficient clinical consultation time, limited number of follow-up appointments, inadequate education provided to patients to allow starting or intensifying insulin therapy, anxiety about injections, fear of self-monitoring, perceived lack of self-efficacy, and inadequate training to perform self-care management. 55–58 This further worsened during the COVID-19 pandemic, especially during its early phases. 39 , 59–62 Consequently, one of the solutions to address these challenges is to implement innovative and flexible initiatives to educate and support patients, especially those receiving insulin and injectable therapy, and to coach patients during the initiation, intensification, and titration of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Physician-related barriers may include their lack of knowledge of updated guidelines, experience of insulin therapy, beliefs and attitudes towards insulin and diabetes management, side effects of insulin therapy (e.g., hypoglycemia and weight gain), and perceptions of patients' attitudes towards insulin therapy (patient's adherence, and wish to prolong non-insulin therapy) [29].…”
Section: Barriers To Insulin Initiationmentioning
confidence: 99%
“…Patient-related barriers include fear of needle and injection phobia, hypoglycemia and weight gain, negative effects of therapy on occupation and social life, the difficulty of administering injections, perceptions of personal failure in self-management, and the effectiveness of therapy [29].…”
Section: Barriers To Insulin Initiationmentioning
confidence: 99%